CLINICAL EVIDENCE OF EFFECT OF GENERAL ANESTHESIA ON DEVELOPING BRAIN OF A CHILD. A SCOPING REVIEW - Suhael Ahmed, Faisal Abdullah Alharbi, Sara Mazen Fahad Alomran, Hayat Alowais, Norah Abdulrahman Alobaid, Reem Abdullah Sulaiman Alnutayfi, Maram Fahaid M Al Hemaidani, Shatha Saad Alasmary, Renad Mohammed Al-Ibrahim, Norah Saleh Alghuwainem; Reoof Mohammed Alotaibi, Ahmed Abdulrahman Ali Alghamdi, Owais AlGhamdi (Chelonian Research Foundation, 2024)
In recent years, the potential ramifications of general anesthesia on the developing brain of a child have garnered attention and concern within the medical community. With growing evidence and ongoing research, this topic explores the clinical findings surrounding the effects of general anesthesia on the neurodevelopment of children, shedding light on the long-term consequences and potential strategies to mitigate any adverse effects. Exposure to general anesthesia in early infancy may result in neurocognitive deficits and learning disabilities in adulthood, according to a number of studies. The prolonged and repetitive administration of anesthesia may disrupt the normal synaptic development and neuronal activity in the developing brain, potentially impairing cognitive functions. To minimize the risks associated with general anesthesia, medical professionals are now exploring alternative techniques such as regional anesthesia and conscious sedation to limit the exposure of developing brains to anesthesia drugs. The effects of general anesthesia on the maturation of the brain are the subject of this review. Keywords- child, pediatric anesthesia, neurodevelopment